Pain and depression in cancer patients: a longitudinal study. (1st April 2011) - Jack, L; Scott, A; Colvin, L; Laird, B; Fallon, M
Abstract : Abstract: Introduction: Although pain and depression co-exist in 36.5% of cancer patients, the precise nature of the relationship between these symptoms requires elucidation. This study aimed to further understanding of the relationship by determining whether improved pain is associated with a significant reduction in depression and increased quality of life in cancer patients. Methods: A secondary data analysis of patients enrolled in pain intervention studies (n=123) was undertaken. Pain, depression and quality of life were measured at baseline and endpoint using the Brief Pain Index (BPI), Hospital and Anxiety and Depression Score (HADS) and EuroQol Thermometer assessment tools respectively. The Mann-Whitney U-test and Fisher's Exact Test were used to statistically analyse score differences between pain response groups. Results: Baseline BPI, HADS and EuroQol scores were well matched between the groups. Patients responding to pain interventions had an average 2.95 point decrease in endpoint HADS scores, contrasting with a 0.89 increase in non-responding patients (score range 0–42). There was a statically significant difference in the endpoint total HADS scores between the two groups (p=0.0015). Similar mean changes in EuroQol scores revealed increased quality of life scores occurring in patients with (10.64) and without (12.41) improved pain. Conclusions: Improving pain results in reduced depression scores. This supports a unidirectional relationship between pain and depression. Further study is required to establish the presence of a bidirectional relationship. Understanding the relationship between pain and depression allows prioritisation of targeted management of co-existent pain and depression, which may improve the clinical care of cancer patients.